Sago Farmer Development Strategy In North Konawe Regency - Rostin, Rostin; Putra, Asrip; Yunila, Yunila; Pariama, Muh.; Fetriani, Fetriani; Zutriana, Zutriana (International Journal of Management and Education in Human Development, 2024)
This research was conducted in North Konawe Regency by taking samples of 3 sub-districts. The selected sub-district samples were 3 sub-districts, namely Oheo, Asera, and Andowia sub-districts. The selection of the 3 sub-districts was based on; 1). Number of sago processing businesses 2). Having land with sago clumps in it, whether cultivated or not. Data analysis in this study used interactive analysis from Milles and Huberman (Milles and Huberman, 2009). The purpose of study This is aiming know utilization sago as source food local and know the development strategy farmer sago in the Regency North Konawe. It is expected become reference for stakeholders’ interest specifically government area Regency North Konawe utilization sago as source local food and development strategies farmer sago. Improvement ability farmer sago in manage sago will can give significant impact to welfare farmer sago which in the end will give Power support to availability food local. Research result conclude, namely: 1). Utilization production sago in the Regency North Konawe is used For food namely " sinonggi " and as material cake traditional that is cake bagea ; 2) For development farmer sago , then need done several factors, namely ; increase skills farmers , improvement roles and functions extension worker , formation group farmer , help equipment processing sago ;